Optimum Synthesis Conditions of High Quality Explosive Emulsifier Sorbitol Monooleate. Issue 6 (May 2019) - Zi-yang, Ding; Gui-zhou, Gu; Xiu-bo, Hu; Dan, Li; Xin-yang, Song
Abstract: Sorbitol monooleate (Span80) is an extensively used explosive emulsifier at present. It is a kind of non-ionic surfactant with low molecular weight polyols, which belongs to water-in-oil emulsifier and has good emulsifying performance. The low-quality oleic acid was used as raw material. In order to optimize the synthesis conditions of Span80, the effects of different types of catalyst, reaction time and reaction temperature on the acid value, saponification value and hydroxyl value of Span80 were investigated, and the synthesis conditions of Span80 were optimized. The results showed that 159g sorbitol and 360g oleic acid, with 0.2% Zinc Oxide as catalyst, reacted with 2.5h at 210°C in vacuum, at this time the acid value, saponification value and hydroxyl value of product Span80 were 5.8mgKOH/g, 154.1mgKOH/g and 207.3mgKOH/g, respectively. This method provided a reference for the synthesis of high quality and low cost emulsifiers, and had important significance for civil emulsion explosive enterprises.